2020
DOI: 10.1098/rsos.190048
|View full text |Cite
|
Sign up to set email alerts
|

Does unfairness sound wrong? A cross-domain investigation of expectations in music and social decision-making

Abstract: This study was interested in investigating the existence of a shared psychological mechanism for the processing of expectations across domains. The literature on music and language shows that violations of expectations produce similar neural responses and violating the expectation in one domain may influence the processing of stimuli in the other domain. Like music and language, our social world is governed by a system of inherent rules or norms, such as fairness. The study therefore aimed to draw a parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…In terms of LFN, previous studies mainly reported that its amplitude is closely related to ambiguity or conflict. Larger negativity reflected the increased difficulty of processing the degree of ambiguity ( Astle et al, 2006 ; Mueller et al, 2007 ; Polezzi et al, 2008 ; Civai et al, 2020 ; Wagner-Altendorf et al, 2020 ). In the present study, when the rich proposed an unfair offer and were stingy, it might lead to a larger conflict with the social norm and cause the mismatch between a large amount of money owned and little money forgone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of LFN, previous studies mainly reported that its amplitude is closely related to ambiguity or conflict. Larger negativity reflected the increased difficulty of processing the degree of ambiguity ( Astle et al, 2006 ; Mueller et al, 2007 ; Polezzi et al, 2008 ; Civai et al, 2020 ; Wagner-Altendorf et al, 2020 ). In the present study, when the rich proposed an unfair offer and were stingy, it might lead to a larger conflict with the social norm and cause the mismatch between a large amount of money owned and little money forgone.…”
Section: Discussionmentioning
confidence: 99%
“…Another component is the LFN, a negative component reaching peak amplitude around 400 ms post stimulus onset over frontal-central areas, which can index the degree of ambiguity or conflict ( Astle et al, 2006 ; Mueller et al, 2007 ; Polezzi et al, 2008 ; Civai et al, 2020 ; Wagner-Altendorf et al, 2020 ). In an object recognition task, Schendan and Kutas (2003) found that LFN was larger for those conditions in which objects were harder to identify.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent study [ 28 ] investigated whether the activation of an expectation system in one domain would influence (by facilitating or reducing) the consequences of expectations in another domain, in other words, whether there exists a ‘domain-general expectancy mechanism’. More specifically, here the authors studied the effects of an unexpected melody on the participants’ sensitivity to the violations of fairness and behavioral reactions to that (by the willingness to punish those who behaved unfairly).…”
Section: Introductionmentioning
confidence: 99%